Arthur and Sherlock : Conan Doyle and the creation of Holmes - Sims, Michael, 1958- (Bloomsbury, 2017)
" As a young medical student, Arthur Conan Doyle studied in Edinburgh under the vigilant eye of a diagnostic genius, Dr. Joseph Bell. Doyle often observed Bell identifying a patient's occupation, hometown, and ailments from the smallest details of dress, gait, and speech. Although Doyle was training to be a surgeon, he was meanwhile cultivating essential knowledge that would feed his literary dreams and help him develop the most iconic detective in fiction. Michael Sims traces the circuitous development of Conan Doyle as the father of the modern mystery, from his early days in Edinburgh surrounded by poverty and violence, through his escape to University (where he gained terrifying firsthand knowledge of poisons), leading to his own medical practice in 1882. Five hardworking years later -- after Doyle's only modest success in both medicine and literature -- Sherlock Holmes emerged in A Study in Scarlet. Sims deftly shows Holmes to be a product of Doyle's varied adventures in his personal and professional life, as well as built out of the traditions of Edgar Allan Poe, ©⁹mile Gaboriau, Wilkie Collins, and Charles Dickens -- not just a skillful translator of clues, but a veritable superhero of the mind in the tradition of Doyle's esteemed teacher. Filled with details that will surprise even the most knowledgeable Sherlockian, Arthur and Sherlock is a literary genesis story for detective fans everywhere. "--